EMPOWERING TEACHER IN UTILIZING ICT-BASED MEDIA THROUGH IN-HOUSE TRAINING (IHT)TO IMPROVE LEARNING QUALITY - Ika Tyasing Kusumawati; Bambang Ismanto; Ade Iriani (Pascasarjana UM, 2019)
Abstract: This research aims to improve the quality of learning by empowering teachers to utilize ICT-based media through IHT. The object of this study was 42 teachers of SMPN 5 Salatiga. This research was a school action research. Data were collected through interviews, questionnaires, and observations. The data analysis were: (1) data reduction, (2) data display, and (3) drawing conclusions. This research revealed that: a) by utilizing ICT-based learning media the quality of learning can be improved; b) the quality of learning in SMP Negeri 5 Salatiga improves by using IHT and it is evidenced by the increase in the average score on each subject.Key Words: ICT-based media, learning quality, in-house training Abstrak: Penelitian ini bertujuan untuk meningkatkan mutu pembelajaran dengan memberdayakan guru dalam pemanfaatan media berbasis IT melalui IHT. Objek penelitian yaitu guru SMP Negeri 5 Salatiga sebanyak 42 orang. Penelitian ini termasuk jenis penelitian tindakan sekolah. Data dikumpulkan dengan wawancara, angket, dan observasi. Analisis data mencakup: (1) reduksi/memilih data, (2) display/menyajikan data, dan (3) kesimpulan. Hasil yang diperoleh dari penelitian yaitu: a) dengan memanfaatkan media pembelajaran berbasis IT mutu pembelajaran dapat meningkat; b) kualitas pembelajaran di SMP Negeri 5 Salatiga meningkat dengan dilakukannya IHT yang dibuktikan dengan meningkatnya capaian rata-rata per mata pelajaran.Kata kunci: Media pembelajaran berbasis IT, mutu pembelajaran, IHT